Розроблення системи контролю параметрів середовища в акваріумі - Григоренко, Ігор Володимирович; Григоренко, Світлана Миколаївна (ВКФ "Фавор", 2019)
Розглянуто вирішення науково-практичного завдання розроблення системи контролю параметрів середовища в акваріумі від створення структурної схеми та алгоритму роботи до розроблення схеми електричної принципової. Проаналізовано фактори, що впливають на життєву діяльність риб в акваріумі та встановлено основні з них, які потрібно контролювати. Проведено розрахунок невизначеності результатів вимірювання встановлених основних параметрів середовища, а саме, температури та рівня розчиненого кисню, який довів можливість забезпечення високої точності та достовірності результатів вимірювань отриманих за допомогою розробленої системи контролю. Така система контролю надає можливість забезпечити відносну похибку вимірювання, не гіршу ніж 0,5 %.

The paper considers the solution of the scientific and practical task of developing a system for monitoring environmental parameters in an aquarium from creating a structural diagram and an algorithm to working up to developing a basic electrical circuit. The factors affecting the livelihoods of fish in an aquarium are analyzed, and the main ones that need to be controlled are established. The uncertainty of the measurement results of the established basic parameters of the medium, namely temperature and dissolved oxygen, was calculated, which proved the possibility of ensuring high accuracy and reliability of measurement results obtained using the developed control system. The developed control system allows to ensure the relative measurement error not worse than 0.5%. The need to develop a control system is connec-ted with the fact that in order to ensure the normal development of fish and plants in the aquarium, it is necessary to create an environment that is as much as possible natural. This requires timely temperature control, as well as control of the pH and dissolved oxy-gen, which is possible only with the help of an automatic control system. The system allows the sending of SMS commands for switching on/off the heating and aeration of water in the aquarium, receiving reports on the condition of the heater and the aerator (on/off) and the measured environmental parameters. It is possible to program, for example, sending messa-ges with abnormal increase or decrease in temperature or the suspicious rate of its change. In the course of the work the structural and electrical principles of the control system were created, the algorithm of its work was being compiled, the uncertainty of the measurement of the main parameters of the environment in the aquarium was carried out, which proved the possibility of providing high accuracy and reliability of the results of measurements obtained with the help of the developed control system.
Development of the System for Control of Environmental Parameters in the Aquarium
Keywords: похибка; невизначеність; точність; схема електричної принципової; system; error; uncertainty; accuracy; control